Effect of ethanol on action potential and ionic membrane currents in rat ventricular myocytes - Bébarová, M; Matejovič, P; Pásek, M; Ohlídalová, D; Jansová, D; Simurdová, M; Simurda, J (Acta physiologica (Oxford, England), 2010)
AIM: Even though alcohol intoxication is often linked to arrhythmias, data describing ethanol effect on cardiac ionic channels are rare. In addition, ethanol is used as a solvent of hydrophobic compounds in experimental studies. We investigated changes of the action potential (AP) configuration and main ionic membrane currents in rat cardiomyocytes under 20-1500 m(M) ethanol. METHODS: Experiments were performed on enzymatically isolated rat right ventricular myocytes using the whole cell patch-clamp technique at room temperature. RESULTS: Ethanol reversibly decelerated the upstroke velocity and decreased AP amplitude and duration at 0.2 and 3 Hz. The fast sodium current I(Na) , l-type calcium current I(Ca) and transient outward potassium current I(to) were reversibly inhibited in a concentration-dependent manner (50% inhibition at 446 ± 12, 553 ± 49 and 1954 ± 234 m(M), respectively, with corresponding Hill coefficients 3.1 ± 0.3, 1.1 ± 0.2 and 0.9 ± 0.1). Suppression of I(Na) and I(Ca) magnitude was slightly voltage dependent. The effect on I(Ca) and I(to) was manifested mainly as an acceleration of their apparent inactivations with a decreased slow and fast time constant respectively. As a consequence of marked differences in n(H) , sensitivity of the currents to ethanol at 10% inhibition decreases in the following order: I(Ca) (75 mm, 3.5‰), I(to) (170 m(M), 7.8‰) and I(Na) (220 m(M), 10.1‰). CONCLUSION: Our results suggest a slight inhibition of all the currents at ethanol concentrations relevant to deep alcohol intoxication. The concentration dependence measured over a wide range may serve as a guideline when using ethanol as a solvent.
Keywords: membránové potenciály; metoda terčíkového zámku; Potassium; Rats; ethanol; látky tlumící činnost CNS; akční potenciály; Ion Channel Gating; iontové kanály; Action Potentials; draslík; vápník; Ethanol; Rats, Wistar; mužské pohlaví; srdeční komory; Patch-Clamp Techniques; Membrane Potentials; Central Nervous System Depressants; Myocytes, Cardiac; krysa rodu Rattus; Calcium; zvířata; rozpouštědla; Heart Ventricles; sodík; gating iontového kanálu; Ion Channels; kardiomyocyty; potkani Wistar; Solvents; Sodium; Male; Animals